2019
DOI: 10.1021/acs.estlett.9b00695
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Polarization Lidar to Profile the Urban Aerosol Phase State during Haze Episodes

Abstract: The phase states of atmospheric aerosol particles affect their physical, chemical, and optical properties. Particles with different phase states exhibit different viscosities and various shapes that cause differences in their scattering polarization. In this study, a novel method for inferring the phase state of submicrometer particles using the particle linear depolarization ratio (δ p ) retrieved from polarization lidar is proposed. The values of δ p during several haze episodes showed good correlation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…All elemental ratios of OA in this study were calculated by the "Improved-Ambient (I-A)" method (Canagaratna et al, 2015) unless specified. The combined data from bypass and TD lines (MS bypass+TD ) were analyzed with positive matrix factorization (PMF) to resolve potential OA factors (Ulbrich et al, 2009). Four factors were identified in the summer of 2018: HOA, COA, less oxidized oxygenated OA (LO-OOA) and more oxidized OOA (MO-OOA).…”
Section: Ams Data Analysismentioning
confidence: 99%
“…All elemental ratios of OA in this study were calculated by the "Improved-Ambient (I-A)" method (Canagaratna et al, 2015) unless specified. The combined data from bypass and TD lines (MS bypass+TD ) were analyzed with positive matrix factorization (PMF) to resolve potential OA factors (Ulbrich et al, 2009). Four factors were identified in the summer of 2018: HOA, COA, less oxidized oxygenated OA (LO-OOA) and more oxidized OOA (MO-OOA).…”
Section: Ams Data Analysismentioning
confidence: 99%
“…The OA volatility is intrinsically related to particle phase state that plays an important role in affecting heterogeneous reactions and the formation of cloud condensation nuclei. Particle phase states have been measured by using three-arm impactor (Liu et al, 2017;Liu et al, 2019) and polarization lidar (Tan et al, 2020) in China in recent years. The results showed that particles are generally in liquid state throughout the year in south China, while there is a transition from semisolid to liquid state as RH increases above 60% in winter in NCP.…”
Section: ;mentioning
confidence: 99%
“…Due to its severe impact on human health and significant atmospheric visibility reduction, Particulate Matter (PM) has attracted increasing attention worldwide (Lelieveld et al, 2015;Gu et al, 2016;An et al, 2019;Zhang et al, 2019;Zhao et al, 2020). The source and composition of PM in the atmosphere are complex, which may be generated directly by the emission sources, or generated by the secondary conversion (Zhao et al, 2018a;Tan et al, 2019). Associated with the different meteorological conditions, the size and composition of PM in the atmosphere vary widely, and could cause various health hazards and weather and climate effects over different locations (Huang et al, 2014;Lelieveld et al, 2015;Liao et al, 2015;Wang et al, 2015;Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%